Surviving as a Community: Antibiotic Tolerance and Persistence in Bacterial Biofilms - Yan, Jing; Bassler, Bonnie L (Cell host & microbe, 2019)
Biofilms are surface-associated bacterial communities that play both beneficial and harmful roles in nature, medicine, and industry. Tolerant and persister cells are thought to underlie biofilm-related bacterial recurrence in medical and industrial contexts. Here, we review recent progress aimed at understanding the mechanical features that drive biofilm resilience and the biofilm formation process at single-cell resolution. We discuss findings regarding mechanisms underlying bacterial tolerance and persistence in biofilms and how these phenotypes are linked to antibiotic resistance. New strategies for combatting tolerance and persistence in biofilms and possible methods for biofilm eradication are highlighted to inspire future development.